Dynamic modelling of rainwater harvesting with green roofs in university buildings. (20th August 2021) - Almeida, Alissandra Pessoa; Liberalesso, Tiago; Silva, Cristina Matos; Sousa, Vitor
Abstract: University buildings may contribute significantly to the urban demand of potable water, particularly in small and medium communities with large universities. In this regard, alternative sources of water supply contribute to minimizing the pressure on natural resources. This paper investigates the applicability of rainwater harvesting (RWH) systems to partially compensate the daily non-potable water demand in university buildings. The traditional daily water balance model was improved to enhance the accuracy of the performance analysis and design optimization of the RWH system by accounting for consumption and runoff variability. The novel algorithm was tested using real daily water consumption data for two university buildings located in Portugal. In addition, different scenarios were evaluated combing RWH systems with extensive green roofs and different runoff distributions over time. The findings indicate that the use of real daily water consumption data instead of average values influences the final results, especially in buildings with fluctuating water consumption patterns over time up to 11%. Regarding the runoff coefficient, it was verified that variable values are recommended compared to the average values. Runoff variability associated with the installation of green roofs was found to decrease RWH system performance due to reduced stormwater runoff. However, the scenario with 50% of the catchment area covered by extensive green roofs showed promising results, decreasing the potential water saving less than 6% and increasing the volume of retained water by almost 15%. Highlights: Rainwater Harvesting (RWH) systems in university buildings increase water savings. The developed hydrologic model allows the inclusion of real consumption patterns. Average demand values are inappropriate for fluctuating consumption patterns. Green roofs (GR) combined with RWH systems proved to be a promising alternative. GR provides additional benefits at building and urban scale.